An Interventional Program for Nursing Staff about Prevention of Corona Virus Disease - Mohammed Rajeh Tarrar, Sabah Abbas Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The objectives of the study is determining the effectiveness of interventional program on nursing staffs’ knowledge about prevention of Covid-19. Methodology: A pre-experimental design (one group design: pre-test and post-test) conducted at Isolation Ward in Al-Diwaniyah Teaching Hospital. The study period from (13th October, 2021 to 4th March, 2022) on a non-probability (purposive) sample consisting of (34 nurses) working in Isolation Ward. Results: The study demonstrated that all the study sample responses at the pre-test were low knowledge with a statistical mean of scores (1.2817). Other than the post-test, the table shows that (100%) of the study sample have high knowledge at the mean of scores (1.8978). Also, the results revealed a highly significant difference between the pre-test and post-test of the study sample after participated in the interventional program at the p-value (0.0001). In addition to, this study indicated that there were significant differences in nursesꞌ knowledge in post-test compared to pre-test (in the post test M= 1.89 versus in the pretest M= 1.28 at p-value 0.0001). Conclusion: The level of nurses’ knowledge was not as required (poor).After giving the interventional program the knowledge of nursing staff was improved.